.2y+.33=.33y-.33

Simple and best practice solution for .2y+.33=.33y-.33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .2y+.33=.33y-.33 equation:


Simplifying
0.2y + 0.33 = 0.33y + -0.33

Reorder the terms:
0.33 + 0.2y = 0.33y + -0.33

Reorder the terms:
0.33 + 0.2y = -0.33 + 0.33y

Solving
0.33 + 0.2y = -0.33 + 0.33y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.33y' to each side of the equation.
0.33 + 0.2y + -0.33y = -0.33 + 0.33y + -0.33y

Combine like terms: 0.2y + -0.33y = -0.13y
0.33 + -0.13y = -0.33 + 0.33y + -0.33y

Combine like terms: 0.33y + -0.33y = 0.00
0.33 + -0.13y = -0.33 + 0.00
0.33 + -0.13y = -0.33

Add '-0.33' to each side of the equation.
0.33 + -0.33 + -0.13y = -0.33 + -0.33

Combine like terms: 0.33 + -0.33 = 0.00
0.00 + -0.13y = -0.33 + -0.33
-0.13y = -0.33 + -0.33

Combine like terms: -0.33 + -0.33 = -0.66
-0.13y = -0.66

Divide each side by '-0.13'.
y = 5.076923077

Simplifying
y = 5.076923077

See similar equations:

| 13a=39 | | 3h+33= | | 52+6x=180 | | 4x+4x^2=68 | | log(2x-1)=10 | | 10-6x-9=2-4(2x+8)-10 | | 5y+10(y+6)+25(y+2)=310 | | x+95-1= | | 3(x+5)+5(x+4)=27 | | 30x^2+24x-25x-20= | | 5y-2x=-13 | | 8x-6x=34 | | Log(x^2-30)-log(x)=0 | | 7n-1=-106 | | (k+5)(2k-3)=2k^2-1 | | 4(-10+70)=44 | | 18-7+1=-9 | | -5x+8=-2x-22 | | 0.08a+0.09(100-a)=8.8 | | 3(5x+1)=26 | | r^2+r=240 | | h^2-148=16h | | 3x^4+x^3-12x^2-4x=0 | | 2x-6=2x-2 | | x=x^2-110 | | 2x-(3-2x)=4+3(2x) | | 3x-5=5x+10 | | -5+-5+2+-5+4=-9 | | f(x)=kx^2-6x+3 | | 1=-3x+20 | | 5p+4=-9 | | 11v+9=130 |

Equations solver categories